2018
DOI: 10.1136/bjophthalmol-2018-313191
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in final visual acuity occur even within the first 3 days after a macula-off retinal detachment

Abstract: PurposeTo determine if final visual acuity (VA) is affected by duration of macular detachment (DMD) within the first week of macula-off retinal detachment (RD).MethodsThis is a retrospective study of eyes that underwent repair within 7 days with vitrectomy or vitrectomy with scleral buckle for macula-off RD at Stanford University Hospital between 1 May 2007 and 1 May 2017. A generalised linear model was constructed using DMD, postoperative lens status, preoperative VA, patient age and surgeon as the independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 17 publications
0
39
0
3
Order By: Relevance
“…Notably, no statistically significant difference in FVA could be seen in patients who obtained surgical treatment within the first 3 days. In contrast, a more recent study by Greven et al [5] proposed a difference of FVA in patients receiving surgical intervention after a duration of 1 day of macular detachment compared to those treated after 3 days of central vision loss. However, both study groups stated that the outcome for surgical timing within the 3 days should be interpreted with great caution, as they had a low sample size of only 35 eyes.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Notably, no statistically significant difference in FVA could be seen in patients who obtained surgical treatment within the first 3 days. In contrast, a more recent study by Greven et al [5] proposed a difference of FVA in patients receiving surgical intervention after a duration of 1 day of macular detachment compared to those treated after 3 days of central vision loss. However, both study groups stated that the outcome for surgical timing within the 3 days should be interpreted with great caution, as they had a low sample size of only 35 eyes.…”
Section: Discussionmentioning
confidence: 91%
“…However, the accurate timing of foveal detachment is a major limitation faced by all studies investigating surgical timing in fovea-off RRDs [1,2,5,9,10]. Most studies investigating the influence of surgical timing used patientreported beginning of central vision loss as a surrogate marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 9 , 10 , 11 Prior studies have suggested a delay of 7 days can lead to worse visual outcomes, while some recent studies have suggested that a delay in even 3 days leads to worse visual acuity outcomes. 12 , 13 The purpose of this report is to investigate the effect of the initial COVID-19 pandemic on the clinical presentation of acute, primary RRD to a tertiary referral-based retina subspecialty practice setting.…”
Section: Introductionmentioning
confidence: 99%
“…During RRD, the outer retina is separated from the RPE and choroid, resulting in marked metabolic derangements partially due to hypoxia. 18,19 In experimental models of RRD, the metabolic injury causes photoreceptor apoptosis that begins within 24 hours and peaks by day 3. 18,20 Greven et al reported that shorter duration of macular detachment is associated with better final visual acuity, even among patients whose detachment is ≤ 3 days.…”
Section: Discussionmentioning
confidence: 99%